SEMANTIC AND STYLISTIC DIFFERENTIATION OF COLOUR TERMS - Bazarbaeva, Albina (Журнал иностранных языков и лингвистики, 2021)
In everyday life, people mainly identify colours by their names and describe their characters by semantic terms, for example, light red, strong blue, etc. Colour names can be employed to generate semantic interpretation, describe the appearance of the image and finally to identify important semantic symbols. In this section, colours are conceptualized as emotions, feelings, reflections and associations due to visual perceptional reasons.